Review of the Properties, Acceptance, and Use of Eucalyptus as an Alternative Species in Ethiopia's Wood Industries - Kaba, Gemechu (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2024)
The demand for forest-related goods and services has continued to grow in Ethiopia due to the increasing population, urbanization, and the boom of the construction sector. In the past, the demand was covered by indigenous timber species, which now have declined due to unwise exploitations. To narrow down the gap between supply and demand an alternative solution is promoting and utilizing fast-growing species such as Eucalyptus wood. To effectively utilize this species identifying its special characteristics, level of acceptance in wood industries, and utilization practices are very important.  To achieve the goals of this review, a thorough search was carried out across multiple scholarly databases. Then, pertinent research, papers, and articles about the use of Eucalyptus in the wood industries were downloaded and reviewed. The study shows that Eucalyptus is widely cultivated in various regions of Ethiopia and plays a significant role in the socio-economic dimensions of many Ethiopians, providing livelihood opportunities, environmental services, and supporting sustainable development. Although it is being used as an alternative to traditional timber species in many places in the world, it is not being widely used in Ethiopia's wood industry for furniture manufacturing. This is because producers are unaware of the special properties of this species; its felling technique, sawing method, and drying behavior which demands proper attention and care. To ensure the sustainable use of Eucalyptus resources, better tree management techniques, innovative wood processing techniques, market development, and strengthening the capacity of relevant stakeholders are imperative.